DIGITAL SEDIMENT COLOUR ANALYSES, DSCA, OF LAKE SEDIMENTS - PITFALLS AND POTENTIALS - Christensen Ja.; Bjorck S. (My University, 2001)
Image analysis of lacustrine sediments has become a useful method in paleolimnology, since correlation between grey-scale and different climate and sediment proxies has turned out to be very promising. Based on experiences obtained during the mounting of a system to perform digital sediment colour analysis, DSCA, a description of the method and its pitfalls are presented. We find that certain factors are important in controlling the recorded grey-scale; the light used, oxidation of the sediment surface, and the way the camera records the colours. These pitfalls are analysed and discussed since they obviously limit the use of the method, but they may also give ideas for alternative ways for using DSCA.
Keywords: LAKE SEDIMENTS; DSCA; IMAGE ANALYSIS; GREY-SCALE; COLOUR VARIATIONS